2008
DOI: 10.1086/527379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of HIV Infection among Female Sex Workers in 2 Mexico–US Border Cities

Abstract: Culturally appropriate interventions are needed to identify and treat ulcerative sexually transmitted infections and reduce HIV risks associated with stimulants among FSWs in the Mexico-US border region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
177
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(187 citation statements)
references
References 14 publications
9
177
1
Order By: Relevance
“…The prevalence of active syphilis, which was associated with four times the odds of HIV infection in a previous study, 26 was dramatically lower among FSWs in our sample (e.g., 14 % in 2006 vs. 1 % in our sample). Although the low prevalence we identified could reflect continued HIV/STI surveillance and prevention efforts throughout the region, 44 we cannot determine from our sample whether HIV/STI prevalence is decreasing in the larger population of FSWs in these cities.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The prevalence of active syphilis, which was associated with four times the odds of HIV infection in a previous study, 26 was dramatically lower among FSWs in our sample (e.g., 14 % in 2006 vs. 1 % in our sample). Although the low prevalence we identified could reflect continued HIV/STI surveillance and prevention efforts throughout the region, 44 we cannot determine from our sample whether HIV/STI prevalence is decreasing in the larger population of FSWs in these cities.…”
Section: Discussioncontrasting
confidence: 71%
“…23 Our research among mostly street-based FSWs in these cities has also revealed high prevalence of STIs: in 2006, 6 % tested positive for gonorrhea, 13 % for Chlamydia, and 14 % for active syphilis (titers≥1:8). 26 Drug use, including injection drug use, which are increasingly common in this region due to "spillover" from trafficking routes, 27 further promote HIV/STI transmission by compromising FSWs' abilities to negotiate consistent condom use. 28 In these cities, FSWs' HIV positivity was associated with smoking, snorting, or inhaling methamphetamine and injecting cocaine, 26 and among FSWs who injected drugs, 72 % tested positive for at least one STI including HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It varied from 14.2% in the US-Mexico border cities to 45.7% in Argentina [1,12,[18][19][20][21][22] . This varied prevalence rates may be due to the different population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing of crack pipesparticularly among individuals with sores on their lips as a result of burns and cuts-may contribute to infectious disease transmission [12,13]. Inhalation of methamphetamine has been associated independently with human immunodeficiency virus (HIV) infection among female sex workers, even after accounting for injection drug use [14]. A recent laboratory study suggests that methamphetamine accelerates HIV replication [15].…”
mentioning
confidence: 99%